BOUTIQUE OWNERS IN NUR-SULTAN: THE THORNY PATH TO SUCCESS FOR WOMEN ENTREPRENEURS - Kimel, Zhansaule (Nazarbayev University School of Sciences and Humanities, 2020)
Many people believe that shuttle trade does not exist anymore and it is a thing of the past. Shuttle trade as an activity in which individual peddlers buy goods abroad and import them for resale in local markets and street shops, was one of the main achievements that created millions of jobs and ensured relative stability at a time of uncertain 1990s. Today’s shuttle trade exists under the guise of various types of business enterprises and legalized entrepreneurship. Sometimes it is still the only income source for many households of post-Soviet Kazakhstan. This thesis asks what the effects of shuttle trade have been on the personal lives of merchant women in Kazakhstan. I focus on the narratives of women and their own evaluation of the impact of trading on their lives. This study focuses on the experience of the women who got involved in shuttle trade after the collapse of the Soviet Union and their perspective on that experience from today’s standpoint. It reveals the losses and challenges that women faced in their lives as merchants. This topic is interesting not only from the perspective of assessing the situation of free market trade activities after the USSR demise, but also from the perspective of analyzing the experience and stories of those merchant women. In this paper, women express their views and attitudes toward their business, life, work, family and also how their life perceptions changed over time. These women were the ones whom, with their hard work, physically created the capitalist market, sometimes without any knowledge and tools. Their contributions to the social and economic development of the country remain highly relevant. I find that despite benefits of shuttle trading for women including financial independence, freedom, and/or social influence, it has also significant costs and brings some regrets. By traveling the road from the small-scale petty trading to successful and legal business ownership, women traders contributed and in some ways shaped the market economy of post-Soviet Kazakhstan. This study will add value to the knowledge of shuttle trade process not from the economic perspective but from the socio-cultural sensitivity. It would be in interest to those who are interested in gender, sociology, culture, to learn the experience of merchant women from their own viewpoint t and understand the role of women in a patriarchal society as Kazakhstan.